Design and Realization of a Controlled Electromagnetic Breaking System - Tchahou Tchendjeu Achille Ecladore; Yungho Edickson Bobo; Nfah Eustace Mbaka (Journal of Engineering)
Industrial machines with sharp moving blades are extremely dangerous to workers. These machines often rotate for some time (called the run-down time) before completely stopping due to little or no brakes. In the case where brakes are used, they are mechanical in nature and are associated with problems of wear out and frequent maintenance among others. In this paper, we proposed a mathematical model and implementation of an electromagnet and design and construction of a mechanical support frame and a controller for the electromagnetic braking system. The electromagnetic braking system works on the principle of electromagnetism. To realize the semicircular electromagnets, we coil the gauge wires several times around a ferromagnetic core material. The electromagnet was connected to a 12 V 7 Ah battery and was used to lift a load whose mass and corresponding weight were predetermined using a scale balance. The magnetic force generated was equal to the amount of maximum load it could lift. The mechanical frame, on which the electromagnets, motor, battery, switches, and chain drive system were mounted, was designed using SolidWorks and constructed by measuring, cutting, and joining of iron materials. A microcontroller and a power MOSFET were used in the control circuit to drive the electromagnet. Major results such as the realized electromagnets and the magnitude of the electromagnetic force (1.43 N) produced by the electromagnets are presented. The mechanical frame and the control circuit are also presented. The braking force was greater than the rotation torque of the disc, and hence braking was achieved.